2010
DOI: 10.1007/s10745-010-9344-0
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Use of Fire and Forest Loss in Canaima National Park, Venezuela. Assessment of and Tools for Alternative Strategies of Fire Management in Pemón Indigenous Lands

Abstract: In Canaima National Park (CNP), Venezuela, a protected area inhabited by the Pemón people, sociocultural and demographic changes have contributed to the apparent unsustainable use of fire, leading to forest and habitat loss. This over-use of fire, together with increased forest vulnerability to fire as a result of global climate change, could put both ecosystems and human well-being at risk. The conflict over fire use derives from the fact that whereas the Pemón depend for their livelihood on the use of fire f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(111 citation statements)
references
References 22 publications
1
103
0
7
Order By: Relevance
“…The main executor has been the hydroelectric company called EDELCA, which developed extensive fire-fighting policies to protect the headwaters of the Caroní river, one of the main water suppliers of the downstream dams (EDELCA, 2004). However, the low effectiveness obtained (about 13% of fires are controlled and extinguished) has called the utility of these expensive measures into question (Sletto, 2008;Bilbao et al, 2010). This low success rate is mainly due to (i) the large extension of the area to monitor; (ii) the high number of daily fires; (iii) a bias in fire control measures focused only in specific locations; and (iv) the anthropogenic character of fires, which make any kind of prevention measures difficult (Rodriguez, 2007;Bilbao et al, 2010).…”
Section: Human Occupancy and Firementioning
confidence: 99%
See 1 more Smart Citation
“…The main executor has been the hydroelectric company called EDELCA, which developed extensive fire-fighting policies to protect the headwaters of the Caroní river, one of the main water suppliers of the downstream dams (EDELCA, 2004). However, the low effectiveness obtained (about 13% of fires are controlled and extinguished) has called the utility of these expensive measures into question (Sletto, 2008;Bilbao et al, 2010). This low success rate is mainly due to (i) the large extension of the area to monitor; (ii) the high number of daily fires; (iii) a bias in fire control measures focused only in specific locations; and (iv) the anthropogenic character of fires, which make any kind of prevention measures difficult (Rodriguez, 2007;Bilbao et al, 2010).…”
Section: Human Occupancy and Firementioning
confidence: 99%
“…However, the low effectiveness obtained (about 13% of fires are controlled and extinguished) has called the utility of these expensive measures into question (Sletto, 2008;Bilbao et al, 2010). This low success rate is mainly due to (i) the large extension of the area to monitor; (ii) the high number of daily fires; (iii) a bias in fire control measures focused only in specific locations; and (iv) the anthropogenic character of fires, which make any kind of prevention measures difficult (Rodriguez, 2007;Bilbao et al, 2010). An evident complication to deal with the problem of fire has been the permanent confrontation between indigenous people and non-indigenous actors with economic and conservation interests in the GS.…”
Section: Human Occupancy and Firementioning
confidence: 99%
“…Furthermore, it showed that the variability in fire behavior, in turn, creates a mosaic of grassland patches with different fire histories, where the recently burned patches act as firebreaks in the propagation of fires that are started in neighboring patches. Based on this research, the authors concluded that the Pemon prescribed burning system reduces the occurrence of dangerous fires and furthers spatial and temporal vegetation heterogeneity (Bilbao et al 2009(Bilbao et al , 2010. Most importantly, this study provided support for Pemon prescribed burning as an appropriate technique for biodiversity conservation and suggested that rather than eliminating Pemon fire management practices, the Pemon burning system is key in preventing potentially large destructive fires in critical conservation areas.…”
Section: Social Validation Of Local Knowledge Of Firementioning
confidence: 75%
“…Since fire is considered to be one of the key risk factors in the Gran Sabana (Bilbao and Vessuri 2006), the project also initiated a paleoecological reconstruction of the landscape history (Leal 2010, Leal et al 2016, an analysis of changes in the vegetation cover and land uses, and a study of fire behavior and its impacts in the Gran Sabana (Bilbao et al 2009(Bilbao et al , 2010 [2] . Results of these studies were presented and discussed at various community assemblies that were part of the joint research activities, which prompted important discussions about the historical and social factors that have caused landscape change in the area.…”
Section: Researching Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation